2011
DOI: 10.1038/eye.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted poor weight gain for birth weight and gestational age as a predictor of severe ROP in VLBW infants

Abstract: Aim To analyze relative weight gain by 2-week intervals up to 6 weeks after birth in order to predict the development of retinopathy of prematurity (ROP) requiring treatment among very low birth weight (BW) infants. Methods A prospective study including infants with BW r1500 g born in a single tertiary intensive care unit over 1-year period was conducted. Body weight measurements were recorded weekly and relative weight gains (g/kg/day) were calculated. The main outcome was development of ROP requiring treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 20 publications
2
25
0
2
Order By: Relevance
“…In addition to varieties in ROP rates in different populations. 19,20 This study is the first that investigates the association between Uu colonization and the development of ROP requiring treatment in preterm infants with BW r1250 g. Our results showed that repiratory tract Uu colonization in addition to BW, duration of MV, and PROM 418 h was independently associated with severe ROP. We demonstrated that persistent positive colonization for Uu was significantly associated with more than five-fold increase in the need for laser surgery.…”
Section: Discussionmentioning
confidence: 60%
“…In addition to varieties in ROP rates in different populations. 19,20 This study is the first that investigates the association between Uu colonization and the development of ROP requiring treatment in preterm infants with BW r1250 g. Our results showed that repiratory tract Uu colonization in addition to BW, duration of MV, and PROM 418 h was independently associated with severe ROP. We demonstrated that persistent positive colonization for Uu was significantly associated with more than five-fold increase in the need for laser surgery.…”
Section: Discussionmentioning
confidence: 60%
“…Currently, low weight gain after premature birth is widely accepted as a predictive factor for later development of ROP, being considered superior to BW and GA alone as predictors. [12][13][14][15][16][17][18] In addition, ROPScore also takes into account the use of oxygen in mechanical ventilation and the need for blood transfusions. All these risk factors are involved in the process of ROP development and can be easily identified by ophthalmologists during the initial ROP screening eye examination.…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection for ROP screening is based on gestational age (GA) and birth weight (BW) as well as repeated eye examinations to find those who need laser treatment. The screening criteria, however, vary between developed and developing countries [2,3,4,5,6,7]. Furthermore, repeated eye examinations are associated with pain and stress for the immature infants [8].…”
Section: Introductionmentioning
confidence: 99%